Pedagogical Competence as a Predictor of a Fun Early Childhood and Elementary School Transition: Pendidikan Anak Usia Dini - Kartika Putri, Dea Ayu; Sugiyo Pranoto, Yuli Kurniawati; Formen, Ali (Universitas Pendidikan Ganesha, 2025)
This study aims to determine the perceptions of kindergarten teachers and grade 1 elementary school teachers regarding the PAUD-SD transition period in terms of teacher pedagogical competence, and what are the effects of pedagogical competence on the enjoyment of the PAUD-SD transition period. This study uses a quantitative descriptive approach. The population used in this study were kindergarten teachers and grade 1 elementary school teachers at the driving school in Semarang City. The research sample was taken using a purposive sampling technique of 35 kindergarten teachers and 35 grade 1 elementary school teachers, data collection was carried out using a questionnaire. This study uses classical assumption tests such as normality tests, linearity tests, independent t-tests and simple correlation tests. The results of the independent t-test produced that there were differences in the perceptions of kindergarten teachers and elementary school teachers regarding the implementation of the PAUD-SD transition period. And these perceptions are the same regarding pedagogical competence as a predictor of the PAUD-SD transition period. In this study, it was found that pedagogical competence influenced the enjoyment of the PAUD-SD transition period. So the higher the pedagogical competence, the higher the PAUD to SD transition. Judicious use of keywords may increase the ease with which interested parties can locate our article.